Primatas não-humanos recebidos em centros de triagem no Nordeste entre 2019 e 2022 - Damasceno, Talita Maria Macedo (2022)
Brazil is home to 19.4% of the more than 700 species and subspecies of non-human primates currently recognized by science, in the northeastern region of the country there are 21 of the 140 species/subspecies that are found in Brazil, which implies a diversity of 15% of Brazilian primates. Approximately 62% of Northeastern primate species are on the Official National List of Fauna Species Threatened with Extinction, due to habitat loss, accidents with electricity distribution networks and removal of individuals for illegal trade. This scenario is one of the factors that explain why these primates are being found in Wild Animal Screening Centers (CETAS). The quantitative and qualitative characterization of official data on the entry of primates into CETAS offers a diagnosis that helps in decisions on the management of rescued wild animals. In this work, we offer an overview of the entry and destination of primates in nine CETAS in the northeast: Alagoas, Bahia/Salvador, Bahia/Porto Seguro, Ceará, Maranhão, Paraíba, Piauí, Rio Grande do Norte and Sergipe. Between 2019 and 2022, 838 primate specimens were registered, with a gradual increase over the years. A total of 20 species in eight genera and 5 families were received, with Callithrix jacchus corresponding to 67.3% of abundance. In Porto Seguro, Bahia and Ceará, CETAS received the greatest diversity of primates. Exotic specimens to the state accounted for 13.4% of the registered individuals, in eight different species. The main type of entry was the redemption category (66%), followed by voluntary delivery (20%). The most common origins were residence (27.4%) and public road (27%). Two thirds of the animals received were healthy and 82.8% of the individuals came from municipalities with more than 50,000 inhabitants. Sapajus libidinosus had a higher than expected number of individuals from municipalities with up to 15,000 inhabitants. The length of stay within the CETAS was high, with a median of more than 100 days for destined individuals and more than 3 years for those who had not yet been destined at the time of the survey. The main destinations were: 55.1% of the primates were released and 20.4% were sent for scientific research. Only 3.34% of individuals received by CETAS in the northeast are classified in categories of concern by the International Union for Conservation of Nature, which may explain the scarce involvement of conservation entities with primates in CETAS. The analysis of the records reveals the logistical difficulties of this type of activity and the need for greater partnership between entities to ensure the best ex-situ maintenance and destination of the more than 2,000 primates received per year in the Fauna Rescue Centers in Brazil.